Capacitation of mouse sperm is modulated by gamma-aminobutyric acid (GABA) concentration - Shouhei KURATA; Yuuki HIRADATE; Kohei UMEZU; Kenshiro HARA; Kentaro TANEMURA (The Journal of Reproduction and Development, 2019)
In mammals, ejaculated sperm acquire their fertilizing ability during migration through the female reproductive tract, which secretes several factors that contribute to sperm capacitation. Gamma-aminobutyric acid (GABA) is a well-known neurotransmitter in the central nervous system, but additionally enhances the sperm acrosome reaction in the rat and cow. However, the detailed effects of GABA concentration on sperm function remain unclear. In this study, we detected the presence of the GABA type A receptor (GABA A) in mouse epididymal sperm by western blot analysis and in the sperm acrosome by immunocytochemistry. We also investigated the effects of GABA on sperm fertilizing ability. We found that GABA facilitated the tyrosine phosphorylation of sperm proteins, which is an index of sperm capacitation. GABA also promoted the acrosome reaction, which was suppressed by a selective GABA A receptor antagonist. We then found that the effective GABA concentration for the acrosome reaction corresponds to sperm concentration, but we did not detect any marked effect of GABA on sperm motility using a computer-assisted sperm analysis system. Using immunohistochemistry, we also detected GABA expression in the epithelia of the mouse uterus and oviduct. Furthermore, we found that the mRNA levels of glutamate decarboxylase (Gad), which generates GABA from L-glutamate, were higher in the oviduct than in the uterus, and that Gad mRNA levels were higher at estrus than at the diestrus stage. These results indicate that the GABA concentration can act as a modulator of the acrosome reaction and sperm capacitation in the female reproductive tract.